The antecedent of trust and satisfaction in e-procurement - Nanang, Herlino; Misman, Ahmad Fatzilah; Zulkifli, Zahidah; Durachman, Yusuf (Solid State Technology, 2020)
The trust and satisfaction of users of electronic-based systems is very important especially in the procurement of government goods and services. Information systems (SI) today are an inseparable part in the scope of administration and management, especially in developing countries, such as Indonesia. The implementation of the e-procurement system in Indonesia has been running since 2004, but there are still many obstacles such as human resources and infrastructure, and this is very influential on the level of satisfaction and trust of users, especially in the procurement and service sectors. Based on data from the 2016 Financial Supervisory Agency (Say: BPK) corruption cases in the procurement sector are very high, so stakeholders doubt whether this system can work properly. Therefore, this study was conducted to determine the level of satisfaction and trust in the adoption of eprocurement in the public sector and whether the trust and the perceived risk affect users significantly. The population sample is using purposive sampling. 85 (43%) is paper based data and 15 (7%) is online ones. In the stage of data analysis with the partial least squares-structural equation modeling (PLS-SEM) method. The results show that, in addition to perceived trust and risk, other factors such as government trust, perceived quality have a positive effect on the use of an procurement system, in other words showing a significant effect. This study can contribute directly or indirectly to the measurement of user satisfaction, especially from the point of view of government procurement in Indonesia.